2018
DOI: 10.1039/c8cp02685h
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic micellar oligomers of amyloid beta peptides play a crucial role in their aggregation mechanisms

Abstract: A deep understanding of the early molecular mechanism of amyloid beta peptides (Aβ) is crucial to develop therapeutic and preventive approaches for Alzheimer's disease (AD). Using a variety of biophysical techniques, we have found that micelle-like dynamic oligomers are rapidly formed by Aβ40 and Aβ42 above specific critical concentrations. Analysis of the initial aggregation rates at 37 °C measured by thioflavin T and Bis-ANS fluorescence using a mass-action micellization model revealed a concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 88 publications
6
38
0
Order By: Relevance
“…These values are in good agreement with previous toxicity studies of the Aβ peptide interacting with N2a cells, which reported viability values of almost 50% at a much higher peptide concentration (10 μM) than that used in our assay [42]. Regarding toxicity with other cell lines, it has also been shown Aβ42 aggregates at 10 μM that were previously incubated for 24 h at 37 °C, provoked a reduction in the cell viability of SH-SY5Y neuroblastoma cells by almost 20% [40], but the effect was To further understand the effect that the amyloid peptide can exert on neuronal cells, we also performed another assay following a different scheme, in which N2a cells were interacting with Aβ-647 aggregates for 20 min and then generated biothiols were detected by the fluorogenic probe. This experiment shows that during the time that the peptide aggregates were interacting with cells, a considerable accumulation of the peptide were formed at certain points of the membrane in accordance with the other results seen in this study.…”
Section: Study Of Cellular Stress Using a Biothiol Probesupporting
confidence: 92%
“…These values are in good agreement with previous toxicity studies of the Aβ peptide interacting with N2a cells, which reported viability values of almost 50% at a much higher peptide concentration (10 μM) than that used in our assay [42]. Regarding toxicity with other cell lines, it has also been shown Aβ42 aggregates at 10 μM that were previously incubated for 24 h at 37 °C, provoked a reduction in the cell viability of SH-SY5Y neuroblastoma cells by almost 20% [40], but the effect was To further understand the effect that the amyloid peptide can exert on neuronal cells, we also performed another assay following a different scheme, in which N2a cells were interacting with Aβ-647 aggregates for 20 min and then generated biothiols were detected by the fluorogenic probe. This experiment shows that during the time that the peptide aggregates were interacting with cells, a considerable accumulation of the peptide were formed at certain points of the membrane in accordance with the other results seen in this study.…”
Section: Study Of Cellular Stress Using a Biothiol Probesupporting
confidence: 92%
“…This aggregation mechanism was observed in transthyretin [262,263], among variants of the amyloid-β peptide [219,264,265], and also in the four-repeat domain of tau (Tau4RD) [266], β2-microglobulin [152], human and bovine serum albumins [267,268], HypF-N [269], FF domain [270], human muscle acylphosphatase [271], apolipoprotein C-II [272,273], and several SH3 domains [228,259,[274][275][276].…”
Section: Aggregation Via a Nucleation-independent Mechanismmentioning
confidence: 90%
“…From a structural point of view, the simplest manifestation of a primary nucleation mechanism is the nucleated polymerization (NP) mechanism. In this case, amyloidogenic monomers aggregate and originate the nucleus, which further grows into amyloid protofilaments and protofibrils through an elongation process involving mostly monomer addition [219][220][221]. This is the preferential mechanism at relatively low protein concentrations favoring the presence of monomeric species in solution.…”
Section: Primary Nucleation Mechanismsmentioning
confidence: 99%
“…[44][45][46][47][48][49] The amphiphilicity of Aβ is itself a cause of its self-association. Several authors have noted the micelle-like nature of some Aβ soluble oligomers, [50][51][52][53][54] and in fibrils, the parallel, in-register nature of the β-sheets tends to minimize the exposure of the hydrophobic domains to the aqueous medium. In addition, it has been shown that a short internal fragment of Aβ, Aβ16-21, forms antiparallel β-sheets when the N-terminus is acetylated, but the orientation flips to parallel and in-register when the N-terminus is octanoylated-a change that also renders the peptide more amphiphilic in monolayers at the air-water interface.…”
Section: Effects Of Lipid Surfaces and Other Amphiphilic Or Hydrophmentioning
confidence: 99%